The Effect of Power and Interpersonal Communication on the Innovation of Primary Teacher in BPK Penabur Jakarta - Magdalena, Susanty; Zulaikha, Siti; Nurjannah, Nurjannah (SAINTIS Publishing, 2019)
The objectives of the research was to study the effect of power and interpersonal communication on the innovation of the primary teachers in BPK PENABUR Jakarta. This research uses a quantitative approach. The research was conducted by survey method with path analysis used in hypothesis testing. The samples of this research were 159 teachers of primary school as a repondents who were selected through simple random sampling. This research uses survey methods with path analysis methods. The process of collecting the data in SDK PENABUR in DKI Jakarta carried out by using a questionnaire. The data obtained are then analyzed using descriptive statistics and inferential statistics. The results of the study: (1) there is a positive direct effect of power on innovation (2) there is a positive direct effect of interpersonal communication on innovation (3) there is a positive direct influence of power on interpersonal communication